UV-degraded polyethylene exhibits variable charge and enhanced cation adsorption - Ryan Bartnick; Shahin Shahriari; Günter K. Auernhammer; Ulrich Mansfeld; Werner Reichstein; Lisa Hülsmann; Eva Lehndorff (PLoS ONE, 2025)
The widespread use of plastics has led to an omnipresence in soils. We aim to understand whether transformation of polyethylene (PE) and polyethylene terephthalate (PET) in the atmosphere alters their surface properties which, after input of microplastics to soil, leads to an increase of reactive surfaces in soils. PE and PET particles (sieved 200–400 µm) were exposed to accelerated UV degradation. Changes in particle size and surface morphology were measured (using electron microscopy) and compared to pH-dependent variation in surface charge parameters (zeta potential and cation exchange capacity). Fourier transform infrared spectroscopy and X-ray photoemission spectroscopy detected the formation of functional groups and surface atomic composition. After 2000 hours of degradation, PE particles reduced in size from 375 ± 117 µm to 8 ± 7 µm, while PET particles showed only a slight decrease in size, from 653 ± 219 µm to 484 ± 274 µm. Reduction of particle sizes correlated with increased absolute zeta potential and a decrease of the isoelectric point. Hydrated surface charge of degraded PE after 2000 hours was unstable under alkaline conditions, related to the formation of carbonyl groups on its surface and increase in hydrophilicity. PET showed fewer surface chemical changes. Especially for degraded PE incorporated in soil, the alteration of its surface can exhibit comparatively one-tenth of the cation sorption power of clay in alkaline environments (≈7.5 vs. 77 cmol c / kg at pH 9), while degraded PET remained comparatively low (≈1.1 cmol c / kg). This study demonstrates that PE undergoes substantial physicochemical changes during UV degradation, increasing its reactivity, while PET remains relatively stable. These findings highlight the need for further studies to differentiate and understand the effects of diverse plastic types on soil ecosystems.